An Examination of the Structure of Verb Phrases in Persian Language - abasali vafaei (Matn/Pizhūhī-i Adabī, 2011)
Language is the most important means of message transmission and has the most application for the social functioning of mankind. The key element and inseparable part of a sentence is the verb and its structure consists of some parts such as: simple verb, prefix, compound, compound prefix, verb phrases, and intransitive verbs. There have been a lot of investigations and discussions about the structure of the verb. However, there hasn’t been a comprehensive research on the structure of verb phrases. This study is aimed at examining the verb phrases according to the viewpoints of grammarians such as (Khanlari, Ahmadi-Givi, Abolghasemi, Anvari, Farshidvard, and Arjang) and linguists such as (Meshkatodini, Bateni, Vahidian Kamyar, and Tabibzadeh). Further, through the analysis and critique of each one, the truth or inaccuracy and the differences of their view points are explored. To this end, this study represents the viewpoints of both traditional and new grammarians and provides a scientific and precise definition for the verb phrases. Finally, it investigates the structure of verb phrases from both semantic and structural perspectives.